The relationship between physical exercise and smoking behavior among Chinese residents aged 16 years and older - Yu Tie; Wen Tian; Yiru Chen; Ruiting Wang; Peng Shi; Xiaosu Feng (Scientific Reports, 2023)
Abstract To explore the relationship between physical exercise and smoking behavior among Chinese residents aged 16 years and older. Analysis based on 29,466 validated cases in the 2018 China Family Panel Studies (CFPS 2018). The chi-square test and Mann–Whitney U test were used for comparative analysis between groups. Logistic regression analysis was used to explore the relationship between physical exercise and smoking behavior. Gender and birth cohort differences in the relationship between physical exercise and smoking behavior were explored based on stratified regression analysis using gender and birth cohort as stratified variables, respectively. Robustness testing based on multiple linear regression analysis using a replacement data approach. There were 8735 cases of smokers among the respondents. After controlling for relevant confounders, there was a significant negative association between physical exercise and smoking behavior among residents [OR 0.718, 95% CI (0.673, 0.765), P < 0.01]. Physical exercise was more significantly associated with smoking behavior among male residents [OR 0.694, 95% CI (0.649, 0.743), P < 0.01], while it was not significantly associated with smoking behavior among female residents [OR 0.901, 95% CI (0.743, 1.093), P > 0.05]. Physical exercise was more significantly associated with smoking behavior in the pre-1948 (OR 0.748), 1959–1968 (OR 0.748), 1969–1978 (OR 0.812), 1989–1998 (OR 0.576) and post-1999 (OR 0.411) birth cohorts, and the association decreased over time and with social change. The results of the robustness test showed that frequency of exercise was significantly and negatively associated with smoking behavior among residents [OR 0.961, 95% CI (0.951, 0.970), P < 0.01]. Physical exercise is negatively associated with smoking behavior among Chinese residents aged 16 years and older, especially among male residents. There is a cohort effect between physical exercise and smoking behavior of the population, that is, the relationship between the two decreases with social change.